Impact of Sars-Cov-2 on access to healthcare by person with disabilities. - Nkosi Nkosi Botha; Fortune Selase Atsu; Edward Wilson Ansah; Cynthia Esinam Segbedzi; Sarah Annim (Public Library of Science (PLoS), 2023)
The Sars-Cov-2 pandemic has ravaged societies at their very core and deepened pre-existing inequalities. Meanwhile, persons with disabilities (PwDs), the most oppressed group in Ghana that live in poor and deplorable conditions are most like to be negatively impacted by the Sars-Cov-2 crisis. Therefore, the aim of this study is to explore how the Sars-Cov-2 pandemic is influencing access to healthcare by PwDs in the Sekondi-Takoradi Metropolis (STM). We collected data from 17 participants, nine from the Ghana Blind Union (GBU), five from Ghana Society for the Physically Challenged (GSPC), and three from the Ghana National Association of the Deaf (GNAD). An interview guide containing 25 items was used to gather data from the participants and we employed Phenomenological Analysis (PA) approach in making sense of the data. PWDs encounter many different barriers like; i) stigma and discrimination, ii) cost and availability of transport, iii) poor attitude of healthcare staff, iv) poor communication, v) hospital environment and equipment, vi) handwashing and sanitizing facilities, vii) unsuitable washrooms, viii) cost of healthcare, ix) registration and renewal of NHIS cards, and x) loss of income as they attempt to seek healthcare during this Covid-19 era in the STM. Covid-19 pandemic has widened the disproportionate and inequality gaps against PWDs in the STM when they attempt to seek healthcare. in the face of this, STM may lead Ghana to lag in achieving the Sustainable Development Goal (SDG) 3.8, which entreats nations to provide quality healthcare for all persons including PWDs. PWDs need education and empowerment to enable them demand for their rights when accessing healthcare. The findings highlight existing gaps in the implementation of the disability law by healthcare facilities in STM and, re-focus the attention of hospital managers in STM to the healthcare needs of PWDs in STM.